Emerging Fluorescent Molecular Tracers to Guide Intra-Operative Surgical Decision-Making - Debie, Pieterjan; Hernot, Sophie (Frontiers in Pharmacology, 2019)
Fluorescence imaging is an emerging technology that can provide real-time information about the operating field during cancer surgery. Non-specific fluorescent agents, used for the assessment of blood flow and sentinel lymph node detection, have so far dominated this field. However, over the last decade, several clinical studies have demonstrated the great potential of targeted fluorescent tracers to visualize tumor lesions in a more specific way. This has led to an exponential growth in the development of novel molecular fluorescent contrast agents. In this review, the design of fluorescent molecular tracers will be discussed, with particular attention for agents and approaches that are of interest for clinical translation.